Correlation between ocular elasticity and intraocular pressure on optic nerve damages - Ko, M. W. L.; Ali, Md. H.; Lam, D. C. C. (Nazarbayev University, 2014)
Optic neuropathy in glaucoma causes visual field loss and blindness [1]. The optic nerve damage in the lamina cribrosa (LC) of the sclera, the primary site of glaucoma, is correlated with the intraocular pressure (IOP) [2]. Literature shows that the optic nerves are sheared at high IOP and the scleral biomechanical properties play an important role in the development and progression of glaucomatous damage to the LC and ganglion cell axons with the optic nerve head (ONH). The aim of this study is to determine and characterize the correlation between the corneal, scleral and ONH elasticity, and intraocular pressure on the optic nerve damages.
Keywords: optic; glaucoma; ocular elasticity; lamina cribrosa; cornea; sclera; intraocular pressure